Service recovery strategies in western based fast food restaurants : a structural equation model test - Ernest Cyril , de Run; Kusyarnadi, Heriyadi (International Journal of Business and Society, 2008)
This paper sets out to confirm a model that depicts the probability that service recovery activities will be carried out by front liners in Western based fast food restaurants. The study used a Juster scale based questionnaire survey format the restaurants customers. Data was then analyzed using exploratory and confirmatory factor analysis utilizing Structural Equation Model. Factor analysis indicated three views of customers termed as Spoken, Minor Action, and Major Action service recovery strategies. The confirmatory factor analysis indicated that the model was of a good fit (.749). The study was limited to respondents in Kuching. Nevertheless the finding has important implications to management and academia. For academics, the findings provide insight into service recovery modeling. A practical application from this study would be the use of Minor or Major Action service recovery strategies to improve customer’s perception of a company after service failure.